Quantum Stem Cell Therapy for Recovery of Liver Disease - Deby Susanti Vinski; CA Schroeter; Marhaen Hardjo; Andi Kurniawan Nugroho; Natasha Cinta Vinski (Journal of World Science, 2024)
Chronic liver diseases pose a significant global health challenge, necessitating the development of novel therapeutic strategies for liver regeneration and functional recovery. Mesenchymal stem cells (MSCs) derived from umbilical cord blood have emerged as promising candidates for liver regeneration due to their multipotent differentiation capacity, immunomodulatory properties, and paracrine effects. This study aims to investigate the efficacy, safety, and underlying mechanisms of stem cell therapy in the recovery and regeneration of liver tissue in patients with liver disease. The research method used is a case study where Mesenchymal Stem Cell therapy offers the potential to modify the natural recovery of Liver function using stem cell-based technology. Case studies were carried out on several Vinski Regenerative Center clinic patients. This review explores the therapeutic potential of umbilical cord blood-derived MSCs in promoting the recovery of liver function in preclinical and clinical settings. We discuss the mechanisms by which MSCs facilitate liver regeneration, including their ability to differentiate into hepatocyte-like cells, modulate immune responses, and secrete trophic factors that promote tissue repair. Preclinical studies demonstrate the efficacy of umbilical cord blood-derived MSCs in ameliorating liver injury, reducing fibrosis, and improving overall liver function. Challenges such as optimal dosing, timing of administration, and long-term monitoring remain to be addressed. Nevertheless, MSCs from umbilical cord blood represent a promising therapeutic approach for liver regeneration and hold great potential for improving outcomes in patients with liver disease.